(untitled) (Comunicação & Inovação, 2023)
Through the bias of Narrative Semiotics and Cultural Studies, this paper analyze how the developmental essay present in the first three cycles of PT administration of Brazilian federal government was represented in science fiction cinema. The corpus is composed by the films O Homem do Futuro (2011), by Cláudio Torres, and Branco Sai, Preto Fica (2014), by Adirley Queirós. The final result demonstrates two antagonistic versions regarding the policies adopted in the analyzed period.